Modelos de governança e organizações esportivas: uma análise das federações e confederações esportivas brasileiras - Ribeiro, Marco Aurélio de Sá (2012)
This thesis analyzes the relationship among governance models for sports Federations and their effectiveness in Brazil, by means of the Stakeholders Theory, and theories about sports organizations. It suggests a governance pattern model for sports entities that can increase their effectiveness in a context which the sport is relevant to the State and society. The making of this thesis is a result of wide data collection, gathered from several sources. By means of a qualitative approach, the author seeked the best possible information as well as a growing awareness on the theme. This was facilitated by the his involvement with the subject, as he has managed the direction of a Sports Federation since 2005 – Vice President of Rio de Janeiro Sailing Federation during 2005-2010, and President of the same organization during 2011-2012. Here, the key Stakeholders in sport are identified and then the parameters for good governance are presented in the following areas: regulation, results, professionalism, transparency and participation. The solution proposed helps to offer more transparency and control over sports organizations, by creating an instrumental rationality which best meets the objective interests of all Stakeholders.